“The Unbroken Fellowship” What Did Khan Boris and Empress Theodora Agree upon? - Bardola, Kostiantyn (Studia Ceranea, 2024)
This article presents a novel hypothesis regarding the events surrounding the Christianization of Khan Boris of Bulgaria. The author proposes the possibility of a marriage between Empress Theodora and Khan Boris, primarily through a reinterpretation of two passages from the Theophanes Continuatus, which also appear in slightly altered forms in the works of other Byzantine authors. These passages have often been dismissed as mere legends lacking historical significance. However, the author contends that they can be viewed as distorted remnants of authentic plans, inviting a reevaluation of their historical value. The findings contribute to a deeper understanding of the complex relationship dynamics that influenced the region’s political landscape during this era, challenging previous interpretations that have often underestimated the intricate interplay of power, diplomacy, and personal relations in medieval statecraft.